Parental Representations of Electronic Games: A Field Study - BOUCENNA, Abdelouafi Zoheir; BENABDELMALEK, Abdelaziz (Journal of Human Sciences, 2025)
This article presents a field investigation on the subject of social representations held by university professors regarding video and electronic games, based on their observations of their children’s practices of these games. In order to uncover the semantic field specific to these representations, the structural approach to social representations was adopted in accordance with the theory of Abric (2003), which relies on hierarchical or ranked structure analysis using the word association technique in response to a stimulus phrase (Vergès, 1992). The EVOC 2006 software was also employed to determine the central core of these social representations. The results of the field investigation revealed that the central core of the representations consists of a set of fundamental concepts including discovery, skill development, adventure, visual and auditory violence, and conflict. In addition to this central core, peripheral elements closely related to it were identified, involving concepts such as addiction, time-wasting, cultural role, and curiosity.